2001
DOI: 10.1002/jmri.1133
|View full text |Cite
|
Sign up to set email alerts
|

T2‐weighted MRI of the female pelvis: Comparison of breath‐hold fast‐recovery fast spin‐echo and nonbreath‐hold fast spin‐echo sequences

Abstract: In 49 patients who had pelvic abnormalities, breath-hold T2-weighted fast-recovery (FR)-fast spin-echo (FSE) (imaging time ‫؍‬ 24 sec) and nonbreath-hold FSE MR images (2 min 8 sec) were compared qualitatively (on a four-point scale) and quantitatively (using signal-to-noise ratios (SNRs) and contrast ratios (ͦ SIs of the lesions-SIs of the myometrium ͦ /SIs of the myometrium)). Motion artifacts were reduced on breath-hold FR-FSE (3.8:3.2 ‫؍‬ breathhold FSE:nonbreath-hold FSE, P < 0.01) and image quality was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…MR protocols for imaging the female urethra can be performed using a pelvic phased-array coil or cardiac coil on a 1.5-or 3-Tesla machine [3], with no need for patient breath hold [4]. The core of the study and most essential sequences are the small field of view (FOV), high resolution, and T2W images in the axial, coronal, and sagittal planes.…”
Section: Mri Protocolmentioning
confidence: 99%
“…MR protocols for imaging the female urethra can be performed using a pelvic phased-array coil or cardiac coil on a 1.5-or 3-Tesla machine [3], with no need for patient breath hold [4]. The core of the study and most essential sequences are the small field of view (FOV), high resolution, and T2W images in the axial, coronal, and sagittal planes.…”
Section: Mri Protocolmentioning
confidence: 99%
“…To compensate for the decrease in signal-to-noise ratios, the application of the 180° and −90° radiofrequency pulses at the end of the spin-echo sequence, so-called fast-recovery pulse should be considered. 10,11 When respiratory-triggered techniques are used, the k space should be filled during a short period at the end-respiratory phase to obtain images with fewer motion artifacts.…”
Section: Introductionmentioning
confidence: 99%
“…Thus we were unable to calculate the SNR of the colon or the CNR between the lesion and normal rectal wall. In other organs, such as the uterus (19) and liver (26), it has been reported that the SNR and CNR of T2W images with the FRFSE sequence are lower compared to the FSE sequence.…”
Section: Discussionmentioning
confidence: 97%
“…However, T2W images obtained with an FSE sequence with shorter TR may suffer from lower SIs due to proton saturation (18). A fast-recovery FSE (FRFSE) sequence has sequential 180°and -90°radiofrequency (RF) pulses that are applied at the end of the FSE sequence to recover saturated spins (19). By using this method, even with shorter TRs (within 2000 msec), BH-T2W images with an acceptable signal-to-noise ratio (SNR) can be obtained.…”
mentioning
confidence: 99%